Penerapan Pendekatan Kelompok dalam Konseling Remaja: Evaluasi terhadap Perubahan Perilaku - Bunda, Indah Permata; Karneli, Yeni; Netrawati, Netrawati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to evaluate the effectiveness of applying a group approach in counseling adolescents to address changes in their behavior. The research method used was quasi-experimental with a pre-test and post-test design to measure behavior changes before and after the group counseling intervention. The research sample consisted of 30 adolescents randomly selected from several high schools in city X using probability sampling methods. The group counseling intervention was conducted over 8 sessions, with each session lasting 90 minutes. Counseling topics included emotional control, communication skills, stress management, and confidence building. Data collection instruments included validated and reliable questionnaires, as well as direct observation by facilitators. Data obtained from the pre-tests and post-tests were analyzed using paired t-tests to determine if there were significant changes in adolescent behavior before and after the intervention. The data analysis results indicated significant positive changes in adolescent behavior after participating in group counseling. These changes included improvements in emotional control, better communication skills, more effective stress management, and increased self-confidence. Additionally, adolescents showed a more positive attitude toward themselves and their social environment.